2015
DOI: 10.1371/journal.pone.0116903
|View full text |Cite
|
Sign up to set email alerts
|

Uptake and Distribution of Soil Applied Zinc by Citrus Trees—Addressing Fertilizer Use Efficiency with 68Zn Labeling

Abstract: The zinc (Zn) supply increases the fruit yield of Citrus trees that are grown, especially in the highly weathered soils of the tropics due to the inherently low nutrient availability in the soil solution. Leaf sprays containing micronutrients are commonly applied to orchards, even though the nutrient supply via soil could be of practical value. This study aimed to evaluate the effect of Zn fertilizers that are applied to the soil surface on absorption and partitioning of the nutrient by citrus trees. A greenho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 39 publications
1
35
0
1
Order By: Relevance
“…B taken up by roots from more concentrated nutrient solution occurs mostly via passive diffusion, in which uptake efficiency of rootstock varieties depends on root anatomical and physiological traits (Wang et al 2015;Mesquita et al 2016). After absorption by the roots, B is transported to the leaves for the subsequent flushes of growth, with only a small proportion of the nutrient being stored in the roots or stems (Papadakis et al 2003(Papadakis et al , 2004Zhou et al 2014), in contrast to that observed for other micronutrients like copper (Zambrosi et al 2013;Hippler et al 2016) and zinc (Hippler et al 2015). There were distinct responses in fruit yield to the B increase in leaves what still depended on the rootstocks.…”
Section: Discussionmentioning
confidence: 99%
“…B taken up by roots from more concentrated nutrient solution occurs mostly via passive diffusion, in which uptake efficiency of rootstock varieties depends on root anatomical and physiological traits (Wang et al 2015;Mesquita et al 2016). After absorption by the roots, B is transported to the leaves for the subsequent flushes of growth, with only a small proportion of the nutrient being stored in the roots or stems (Papadakis et al 2003(Papadakis et al , 2004Zhou et al 2014), in contrast to that observed for other micronutrients like copper (Zambrosi et al 2013;Hippler et al 2016) and zinc (Hippler et al 2015). There were distinct responses in fruit yield to the B increase in leaves what still depended on the rootstocks.…”
Section: Discussionmentioning
confidence: 99%
“…In most countries, production of legumes and seafood is the most efficient while the production of beef is the least efficient in terms of Nr use678923 (Table 1, Supplementary Table 4). Although vegetables and fruits have large VNFs because of low N use efficiency in these production systems2425, the Nr loss per serving of vegetables or fruits is low due to the very low N content compared to other food types9. Beef production is the least efficient way of using N and supplying dietary protein in most countries that have completed their calculation of VNFs678923, mainly due to the large feed requirements and their high basal metabolic rate26.…”
Section: Discussionmentioning
confidence: 99%
“…During the course of the experiment, both macroand micronutrients were applied via a nutrient solution modified according to Hippler et al (2015b). The supply of macronutrients took place over the course of 40 applications, from transplantation up to 180 days after starting treatments, and micronutrient supply with…”
Section: Plant Growth Conditions and Treatmentsmentioning
confidence: 99%
“…Plants in Experiments I (B) and II (Zn) developed new shoots from the main stem after the harvesting of aerial parts in the first part of the experiment, where enzymatic activity analysis was performed on the leaves. During this new period, ten maintenance fertilizations with micro-and macronutrient were applied via a nutrient solution modified according to Hippler et al (2015b). Completely expanded and mature leaves developed 70 days after harvest, which then received a new foliar application of treatments that was repeated after another 70 days following the first application.…”
Section: Enzymatic Analysismentioning
confidence: 99%